2021
DOI: 10.1186/s13049-021-00920-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes after electrical injury – a retrospective study

Abstract: Introduction People exposed to electrical injuries are often admitted to hospital for observation. Current evidence suggests that patients who have a normal ECG on admission after a low-voltage injury, with no loss of consciousness or initial cardiac arrest may be discharged home after a short observation time. Currently, there are no established standards for the duration of monitoring after electric shock, but 24 h of observation is the most commonly adopted approach. We carried out a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…An initial elevated troponin was observed in 17/533 (3.2%) of patients. In total, 197/533 patients (37.0%) received a new troponin assay at a median of 6 [ 4 11 ] hours after the first assay. Eight presented an increase of the initial troponin (including 6 patients with initial positive troponin).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial elevated troponin was observed in 17/533 (3.2%) of patients. In total, 197/533 patients (37.0%) received a new troponin assay at a median of 6 [ 4 11 ] hours after the first assay. Eight presented an increase of the initial troponin (including 6 patients with initial positive troponin).…”
Section: Resultsmentioning
confidence: 99%
“…Most cardiac events occur immediately after the accident resulting from the proarrhythmic effect of electric shock, but delayed ventricular arrhythmias have also been reported in rare cases [ 10 ]. Most studies did not report a delayed events [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…which can be classified by the underlying voltage as low-voltage (< 1000 alternating current or < 1500 direct current) and high-voltage (≥ 1000 alternating current or ≥ 1500 direct current) injuries. 2,3 These injuries, depending on a wide range of factors, are diverse, and often associated with high morbidity and mortality, ranging from minor skin burns to extensive life-threatening injuries of internal organs causing immediate respiratory and cardiac arrest. 4 In survivors, a particular concern relates to cardiac disturbances, arrhythmias, heart failure, cardiomyopathy, and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…4 In survivors, a particular concern relates to cardiac disturbances, arrhythmias, heart failure, cardiomyopathy, and myocardial infarction. 2,5,6 The Occupational Safety and Health Administration (OSHA) reported that electrical injuries are the third leading cause of occupation-related deaths in the United States. 2 The reported mortality associated with electrical injuries ranges from 1% to 9.1%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation